Efficiency and Profitability of Islamic Bank : Case Study of 9 Banks in Malaysia - Nor Ermawati, Hussain (2011)
Islamic banking system is a field that an interesting to study because this system is based on Islamic law, while the conventional system is based on riba. Islamic banks almost have a competition from conventional banks that have grown rapidly over the last 20 years ago. There are many of the conventional banks in Malaysia such as Affin Bank Berhad, Alliance Bank Malaysia Berhad, Citibank Berhad, EON Bank Berhad, Public Bank Berhad, OCBC Bank (Malaysia) Berhad, Maybank, dan others. This study is focus on the efficiency and profitability of Islamic bank in Malaysia. This study was conducted on 9 bank in Malaysia which also implementing the Islamic Banking system in each branch. Among the 9 banks in this study were Bank Islam Malaysia Berhad (BIMB), Bank Muamalat Malaysia Berhad, Alliance Islamic Bank Berhad, EONCAP Islamic Bank Berhad, HSBC Amanah Malaysia Berhad, Malayan Islamic Banking (Maybank), OCBC Bank Al-Amin, Public Bank Berhad dan RHB Islamic Bank Berhad. The methodology that use in this study is descriptive analysis and econometric methods using data from annual reports of the banks. This study focuses more on efficiency and profitability at Islamic Banks. These results indicate that there are many differences in the efficiency and profitability of the bank's Islamic banking system is implemented either in the way of banking operations, products and services, achievements and many others. In addition, according to this study found that there weaknesses in the system of Islamic banking in Malaysia and should be repaired in order to continue to compete with conventional banking at this time. So, several proposals have been submitted to Islamic banking in Malaysia in order to correct these weaknesses as well as aim to encourage people to make transactions based on Islamic banking.